Encyclopedia of feminist theories - Code, Lorraine (Routledge, 2000)
The path-breaking Encyclopedia of Feminist Theories is an accessible, multidisciplinary insight into the complex field of feminist thought. The Encyclopedia contains over 500 authoritative entries commissioned from an international team of contributors and includes clear, concise and provocative explanations of key themes and ideas. Each entry contains cross -references and a bibliographic guide to further reading; over 50 biographical entries provide readers with a sense of how the theories they encounter have developed out of the lives and situations of their authors.